2015
DOI: 10.1002/pmic.201500025
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and functional characterization of the first Nα‐acetyltransferase in plastids by global acetylome profiling

Abstract: Protein Nα-terminal acetylation represents one of the most abundant protein modifications of higher eukaryotes. In humans, six Nα-acetyltransferases (Nats) are responsible for the acetylation of approximately 80% of the cytosolic proteins. N-terminal protein acetylation has not been evidenced in organelles of metazoans, but in higher plants is a widespread modification not only in the cytosol but also in the chloroplast. In this study, we identify and characterize the first organellar-localized Nat in eukaryot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 48 publications
(99 reference statements)
1
95
0
Order By: Relevance
“…NAA80/NatH differs in that Nt-acetylation of actin occurs posttranslationally since it constitutes the final step of a unique step-by-step mechanism for Nt-maturation. Posttranslational activity is also suggested for the other more recently identified NATs, NAA60/NatF and NAA70/NatG due to their subcellular localization [8,9]. Contrary to the typical NAT, NAA80/NatH appears to be highly selective with actin as the only substrate in vivo in animals, as demonstrated by the lack of actin Nt-acetylation in NAA80 KO cells by COFRADIC analysis [6].…”
Section: Naa80 Acetylates Actin’s N-terminusmentioning
confidence: 96%
“…NAA80/NatH differs in that Nt-acetylation of actin occurs posttranslationally since it constitutes the final step of a unique step-by-step mechanism for Nt-maturation. Posttranslational activity is also suggested for the other more recently identified NATs, NAA60/NatF and NAA70/NatG due to their subcellular localization [8,9]. Contrary to the typical NAT, NAA80/NatH appears to be highly selective with actin as the only substrate in vivo in animals, as demonstrated by the lack of actin Nt-acetylation in NAA80 KO cells by COFRADIC analysis [6].…”
Section: Naa80 Acetylates Actin’s N-terminusmentioning
confidence: 96%
“…Interestingly Met-retention on chloroplast proteins has previously been linked to protein instability (Giglione et al, 2003), whilst fMet can act as a destabilizing residue in bacteria, and possibly also chloroplasts (Piatkov et al, 2015). Cotranslational and posttranslational Nt-acetylation also occurs on chloroplastic proteins, which appears to enhance protein stability (Bienvenut et al, 2011); recently a nuclear-encoded chloroplast-targeted NAT that probably catalyses this modification has been identified (Dinh et al, 2015). Accumulating evidence points towards a relationship between N-termini and protein stability in plastids.…”
Section: The N-terminus As a Stability Determinant In Plastidsmentioning
confidence: 99%
“…The majority of proteins in plants and other eukaryotes are N-acetylated, and a NAT-A loss-of-function Arabidopsis mutant showed pleiotropic developmental and growth defects in Arabidopsis (Ferrández-Ayela et al, 2013), whereas loss of function of NAT-C showed reduced plant growth and photosynthetic capacity (Pesaresi et al, 2003). A chloroplast NAT enzyme (AtNAA70) was recently identified in Arabidopsis and showed N-a-acetylation when expressed in Escherichia coli, in particular for Met, Ala, Thr, and Ser (Dinh et al, 2015). Comparing this specificity with in vivo Arabidopsis chloroplast N-terminome data (Zybailov et al, 2008) suggests that additional NATs operate in chloroplasts (Dinh et al, 2015).…”
Section: N-terminal Acetylationmentioning
confidence: 99%
“…A chloroplast NAT enzyme (AtNAA70) was recently identified in Arabidopsis and showed N-a-acetylation when expressed in Escherichia coli, in particular for Met, Ala, Thr, and Ser (Dinh et al, 2015). Comparing this specificity with in vivo Arabidopsis chloroplast N-terminome data (Zybailov et al, 2008) suggests that additional NATs operate in chloroplasts (Dinh et al, 2015). Because the majority of proteins undergo N-terminal acetylation, it is unclear to what extent this PTM is really regulated (Starheim et al, 2012).…”
Section: N-terminal Acetylationmentioning
confidence: 99%